Beliefs and viewpoints of family medicine physicians on approaches to identify and treat medically unexplained symptoms - Ivetić, Vojislav; Poplas Susič Tonka; Pašić Klemen; Selič, Polona (Acta Medico-Biotechnica, 2021)
Purpose: The purpose of our study was to identify the beliefs and viewpoints of family medicine physicians (FMPs) on the approaches to identify and treat medically unexplained symptoms (MUS). Methods: We used qualitative and quantitative research methods, and prepare a purposive sample for the implementation of five focus groups (three in Maribor and two in Ljubljana) between July and September 2011. The findings were used as questions in the quantitative part of the study applying random sampling (n = 90). FMPs were invited throughout Slovenia to participate in our study (January – March 2012). Analysis of qualitative material was performed using ATLAS.ti 7 software, and quantitative data were statistically processed using SPSS 21.0. Results: In the process of coding, we created 64 codes, which were categorized into 8 categories. In the quantitative part, we received responses from 63 (70%) of the invited FMPs, 84.1% (n = 53) and 77.8% (n = 49) of whom stressed the importance of MUS prevention and treatment, and the importance of good communication, respectively. Of the 63 FMPs, 93.7% (n = 59) were of the opinion that patients with MUS leave feeling exhausted. As potential reasons for MUS, FMPs described problems in patients’ interactions with their surroundings (100%, n = 63), past and current stressful events (96.8%, n=61), and occult psychiatric diseases (68.3%, n = 43). The quality of MUS patient care would improve with more education in the field of basic psychotherapeutic techniques, difficult patient approaches (95.2%, n = 60), and communication skills (95.2%, n = 60). Conclusion: We found that Slovenian FMPs place a strong emphasis on prevention and treatment of patients with MUS, and these patients generally leave them feeling tired and frustrated.